2019
DOI: 10.1039/c9nj03288f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new triazole linked carbohybrids with ROS-mediated toxicity in breast cancer

Abstract: Carbohybrids are an important class of molecules which exhibit diverse biological activities. New coumarins and quinolones linked carbohybrids are synthesised which are showing selective anticancer activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…As noted earlier, derivatives of coumarin-triazole 15 exhibit anti-breast cancer activity 58 . Kraljevic et al.…”
Section: Biological Activitiesmentioning
confidence: 72%
See 4 more Smart Citations
“…As noted earlier, derivatives of coumarin-triazole 15 exhibit anti-breast cancer activity 58 . Kraljevic et al.…”
Section: Biological Activitiesmentioning
confidence: 72%
“…The anticancer activity of the newly synthesised triazole-linked N -glycosides of coumarins and quinolones was determined by Kumari et al. 58 Compound 6 ( Figure 4 ) displayed low micromolar (IC 50 = 10.97 µM) and selective toxicity against MCF-7, a breast cancer cell line. Further study revealed that the anticancer activity of the active compound was due to the formation of reactive oxygen species (ROS) however without significant nuclear DNA damage.…”
Section: Biological Activitiesmentioning
confidence: 99%
See 3 more Smart Citations